Seasonal variation in the concentrations of Cu, Cd, Pb & Zn in Arctica islandica (Mollusca: Bivalvia) from Kiel Bay, Western Baltic - Swaileh, Khalid (Palgrave Macmillan, 1996)
Marine Pollution Bulletin, Vol. 32, Nos 8/9, pp. 631-635, 1996 Seasonal variations in the concentrations of Cu, Cd, Pb and Zn in soft dry tissues of the ocean quahog, Arctica islandica, from Kiel Bay, Germany were studied. Significant monthly variations in the concentrations of the four metals were observed. The two essential metals, Cu and Zn, had their maximum values during the summer months, when the dry soft tissue weight of A. islandica was reaching its maximum values as well. The highest values of the non-essential metals, Cd and Pb, were observed in winter when the dry soft tissue weight of A. islandica was reaching its minimum values